2021
DOI: 10.1080/0886022x.2020.1871369
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of objective sleep quality in older peritoneal dialysis patients

Abstract: Background Sleep disturbance is a prominent concern in dialysis patients and detrimentally impacts clinical and self-reported health outcomes. This study aimed to collect sleep data from in-home actigraphy and to explore possible predictors of sleep quality in older peritoneal dialysis patients. Methods This was a cross-sectional study. Peritoneal dialysis patients aged ≥60 years participated in this study. For each participant, sleep quality was assessed by analyzing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…These age-related alterations can exacerbate sleep difficulties in older HD patients. In line with this study, poor sleep quality and reduced sleep efficiency were both identified in elderly patients on peritoneal dialysis (Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…These age-related alterations can exacerbate sleep difficulties in older HD patients. In line with this study, poor sleep quality and reduced sleep efficiency were both identified in elderly patients on peritoneal dialysis (Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…The resulting tension is a crucial factor contributing to poor sleep quality (De Silva et al, 2021). (ii) More than half of the subjects in this survey were elderly, and advanced age was associated with an increased likelihood of sleep difficulties (Viola et al, 2012; Zhang et al, 2021). (iii) comorbidities such as restless legs syndrome and dialysis adequacy in patients with kidney disease are important contributors to the severity of sleep problems in this population (Kalantar‐Zadeh et al, 2022; Örsal et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Sleep disorders in patients on PD include altered sleep architecture, sleep apnea, restless legs syndrome, periodic limb movement disorder, and excessive daytime sleepiness [ 27 ]. In elderly patients undergoing PD, higher hemoglobin and lower serum phosphorus were significantly correlated with better sleep efficiency, and age was the only significant predictor of the total sleep time [ 28 ]. Furthermore, although APD is more likely to interrupt sleep compared with CAPD, it has been considered effective for sleep apnea [ 29 ].…”
Section: Discussionmentioning
confidence: 99%